INUNDATION PREDICTION AS THE EFFECT OF RISING MEAN SEA LEVEL AND HIGH ASTRONOMICAL TIDE IN NORTH JAKARTA BASED ON 2013-2021 TIDAL DATA - Zahra, Fathima Asyahidatu; Hermana, Joni (Devotion : Journal of Research and Community Service, 2024)
Future sea level rise in North Jakarta is one of the potential hazards that threaten the safety of coastal communities and infrastructure. Prediction of sea level rise is needed to reduce the vulnerability of the people living on the coast. This study was conducted to estimate the height of sea level rise in 2045 using linear regression analysis of hourly tidal data for 2013-2021 coupled with the highest astronomical tide value from the results of tidal harmonic analysis in 2021 using the t_tide application in matlab. The water elevation was then projected on the Digital Elevation Model to obtain the inundation area in 2045. The result of this study is an inundation area of 56 km2 in North Jakarta in 2045 due to an increase in total sea level of 117 cm at high tide.